2022
DOI: 10.1155/2022/1504463
|View full text |Cite
|
Sign up to set email alerts
|

Value of Intravoxel Incoherent Motion (IVIM) Imaging for Differentiation between Intrahepatic Cholangiocarcinoma and Hepatocellular Carcinoma

Abstract: Efficient noninvasive imaging techniques in the differentiation of intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) are very important because of their different management and prognosis. Our purpose was to evaluate the difference of parameters extracted from intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) between the two groups and their performance for the differentiation, as well as the significance of perfusion information. IVIM studies (9 b-values) in 41 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Effective diagnosis is an important prerequisite for formulating treatment measures and evaluating curative effect. Therefore, it is particularly necessary to conduct timely, accurate, and effective examinations and study the patient ‘s disease-related indicators [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective diagnosis is an important prerequisite for formulating treatment measures and evaluating curative effect. Therefore, it is particularly necessary to conduct timely, accurate, and effective examinations and study the patient ‘s disease-related indicators [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,35,36,61 Additionally, IVIM-DWI holds potential value in the evaluation of recurrence risk and therapeutic effect of liver tumors. 83,84 However, IVIM-DWI may not be reliable in the stage of liver fibrosis, 54,55 HCC histological classification, and the distinction of malignant hepatic tumors with diverse pathological types, 29,72,76 which may be due to the inherent drawbacks of the IVIM model. First, IVIM assumes that microcapillary perfusion follows a random pattern similar to water diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…IVIM‐derived parameters can also be used to differentiate hepatic malignancies with distinct pathological characteristics. The correlation of PF and arterial enhancement degree, as well as the extent of hepatic nodule enhancement allow for differentiation of different types of focal hepatic lesions 29,67,72 . Prior studies have suggested the utility of IVIM‐derived parameters for distinguishing between intrahepatic cholangiocarcinoma (ICC) and HCC 65,67,73 (Fig.…”
Section: Liver Focal Lesionsmentioning
confidence: 99%
“…Thus, assessing the degree of ICC differentiation through preoperative imaging can help physicians select an appropriate treatment and improve patients' survival rates. Current research on ICC is dominated by hepatocellular carcinoma (HCC) differentiation [4][5][6][7] . Studies on machine learning based on radiomic features to preoperatively predict histological differentiation of mass-forming ICC are scarce [8] .…”
Section: Introductionmentioning
confidence: 99%